Determination of optimum concentration of lime slurry for soil stabilisation - Abdullah, Muhammad Sofian (2006)
Lime has been used as active additive in soil stabilisation for the past 5000 years ago. The Pyramids of Shersi in Tibet were built using compacted mixtures of clay and lime. Lime powder is normally spread on the ground using mechanical means before mixing with the soil. The problem arise from lime mixing is dusting. The introduction of lime slurry method for soil stabilisation is intended to solve the problem. This research is focused on determination of optimum concentration of the lime slurry for soil stabilisation. Classification test on the natural soil was conducted to determine the suitability of soil to be treated with lime. Suitability of lime test also conducted to ensure the quality of lime used is acceptable. The compaction characteristic of soil treated with lime slurry posses the same behaviour as demonstrated by soil treated with dry lime where the optimum moisture content increases and the maximum dry density decreases. Unconfined compressive test (UCT) was conducted on soil treated with different range of lime concentration, ranging from 10 to 40 percent of weight of water and cured for 7 to 28 days. Based on UCT, it was illustrated that the strength development before 14 days is less significant. This could be due to the process of modification. However, after 14 days the strength increases rapidly. This phenomenon could be related to the process of stabilisation. The optimum concentration of lime slurry to stabilise the soil is 20 percent of weight of water, which is equivalent to 3.63 percent of dry lime.